PENERAPAN ILMU PENGETAHUAN DAN TEKNOLOGI MESIN PENGUPAS KULIT ARI KEDELAI JENIS SCREW PADA INDUSTRI KECIL TEMPE - Andika Wisnujati (Teknoin, 2016)
Soybeans are nutritious foods that contain lots of protein. Foods made from soy beans that are often found is tempeh. The process production tempeh in Indonesia, both in industries or traditional scale are basically similar. The difference lies in the way of peeling the cuticle soybean seeds. Peeling skin soybeans traditionally have weaknesses, among others, in terms of time this process takes a long time, and in terms of cleanliness and health of the process is very unhygienic.  It is necessary to develop technologies and equipment to peeling the husk, clean and hygienic. The purpose of this study is to determine the optimum rotation soybeans the cuticle peeler and economic analysis. The design of manufacturing soybean the cuticle peeler using a variable rotation speed (rpm) based on the diameter of pulley: 10, 8, 7, 6, and 5-inch, clearance space: 2.0; 2.25, and 2.5 mm. The result is a soybean seed husk is peeled and cut into 2 (two). Manufacturing peeler cuticle of soybean type of screw and the high of pegs for soybean industry began with the design of forms, image design, selection of materials and processed with standard production equipment and test its performance. Optimization testing soybean peeler the cuticle by the rotation speed between the end of the peeler cylinder (cylindrical mill) with the body cylinder mill with a production capacity and testing variations size of pulley. Based on the test results it can be concluded that the optimal results peeler cuticle of soybean type of screw, the rotational speed in 386 rpm and 10 inches in diameter pulley and also in 2.5 mm of clearance space.